Comparison of GHG emissions and farmers’ profit of large-scale and individual farming in rice production across four regions of Thailand - Noppol Arunrat (2022)
A large-scale agricultural extension program in Thailand is established under the economy of scale concept. In this study, we used the life cycle assessment concept for greenhouse gas emissions (LCA-GHG) to evaluate and compare GHG emissions from individually farmed units and large-scale farming operations. Results showed that large-scale farming resulted in GHG emissions 11% lower than those arising from individual farming. Moreover, reducing rice seed and transportation used were outstanding under large-scale farming. Production cost was reduced by 28.3%, whereas farmer's profit was increased by 31.2%. Producing rice seed, open windrows compost, manures, and bio-fermented juice for using inside the farm gate had potential to mitigate GHG emissions by 40.7 (−85.9%), 732.3 (−12.3%), 188.8 (−46.8%), and 115.6 (−75.4%) kg CO2eq ha−1 year−1, respectively. Our findings proved that minimal use of external inputs by producing raw materials from co-product and recirculating in the paddy field can reduce GHG emissions and enhance farmers’ profits, especially in large-scale farming. Based on these findings, we propose that merging individual farm units into large-scaled units should be encouraged.